General-Purpose Data Acquisition Cards Based on FPGAs and High Speed Serial Protocols - Giannuzzi, Fabio <1986> (Alma Mater Studiorum - Università di Bologna, 2016)
This thesis exhibits the results of my PhD Apprenticeship Program, carried out at the “Marposs S.p.a.” firm, in the electronic research division, and at the Department of Physics and Astronomy of the Bologna University, in the INFN's electronics laboratories of the ATLAS group. During these three years of research, I worked on the development and realization of electronic boards dedicated to flexible data acquisition, designed to be applied in several contexts, that need to share high performance FPGAs and high-speed serial communications. The thesis describes the successful application of high-speed configurable electronic devices to two different fields, firstly developed in the particle physics scenario, and then the industrial measurement of mechanical pieces, reaching the main goal of the PhD Apprenticeship Program. The common denominator is the development of high speed electronics based on FPGAs for demanding data acquisition and data processing applications. The thesis describes the contribution to the luminosity monitor of LHC at CERN and illustrates a multi-camera system developed for automatic inspection of mechanical pieces made by a machine tool. The Apprenticeship Program allowed me to continue my academic course in parallel with my working activity, giving me the opportunity to finalize the project started during my internship and thesis for my master degree. It also allowed me to achieve a higher level in education and training in two different contexts of excellence, i.e. the industrial company and the academic research, where I concretely learned the best technical knowledge. The chance of bringing together two distant worlds was the most enthusiastic aspect of this PhD research. The world of industry and academic research face similar problems but with different points of view and goals. I had the opportunity to explore pure academic research, and also to apply the knowledge acquired in these years to the industrial research.